2004
DOI: 10.1177/000331970405500202
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Contrast-Enhanced Magnetic Resonance Angiography of the Lower Extremity

Abstract: The aim of this prospective study was to evaluate the feasibility and clinical use of time-resolved magnetic resonance angiography (MRA) of the lower extremity compared to intraarterial digital subtraction angiography (IA-DSA). Twenty-two patients suffering from peripheral arterial occlusive disease underwent MRA and IA-DSA. MRA examinations were performed on a 1.5 T system equipped with a 4-element-array coil. The area from the distal abdominal aorta to the distal lower limb was covered by 2-3 examination ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Our study showed comparable results of average sensitivity of 95% and specificity of 91% with 93% accuracy, respectively. The interobserver agreements on MRA in our study for all grades of arterial stenosis (grades 1–4) with linear weighting is good (k = 0.77), while excellent for hemodynamically significant stenosis without weighting (k = 0.82), which were comparable to the data reported in the literature (14–16, 24).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our study showed comparable results of average sensitivity of 95% and specificity of 91% with 93% accuracy, respectively. The interobserver agreements on MRA in our study for all grades of arterial stenosis (grades 1–4) with linear weighting is good (k = 0.77), while excellent for hemodynamically significant stenosis without weighting (k = 0.82), which were comparable to the data reported in the literature (14–16, 24).…”
Section: Discussionsupporting
confidence: 88%
“…To eliminate the possible venous contamination, and to ensure optimal imaging of each leg in patients where transit times to one foot are markedly different from those to the other, time‐resolved imaging of contrast kinetics (TRICKS) sequence of MRA with three separate contrast injections was initially applied (14, 15, 24). The short acquisition time of 6–10 s with up to 20 phases can take images from early arterial phase to venous phase with the diagnostic sensitivity of 89–97%, and specificity of 97–98%, respectively (14, 15). Andreisek et al performed a hybrid technique combining bolus‐chase and TRICKS sequences by two separate contrast injections also obtained a good diagnostic performance (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sufficient saline flush also helps to lengthen the contrast bolus (62). Suggested flush volumes are 15–50 mL, with most authors using 20 mL (63, 64).…”
Section: Hand Vs Power Injectionmentioning
confidence: 99%